REGULATION OF ACTIN CYTOSKELETON AND FOCAL ADHESION DYNAMICS BY INTERNAL AND EXTERNAL FORCES IN VASCULAR SMOOTH MUSCLE CELLS. (21st November 2014) - Pieri, M; Mekhalfia, A; Platt, M; Ohanian, J; Ohanian, V
Abstract : Introduction: Aberrant sensing and transmission of force by vascular smooth muscle cells (VSMC) results in vascular remodelling, increased arterial stiffness and hypertension. Actin cytoskeleton (CK) remodelling is essential for VSMC responses to vasoconstrictors and mechanical stimuli. Focal adhesions (FAs) link the extracellular matrix and the actin CK allowing sensing and transmission of force. Hic-5 is highly expressed in VSMC and regulates FA assembly and actin CK remodelling in arteries. Aims: To investigate whether alterations in intracellular force generation (actin CK remodelling) or extracellular forces (substrate stiffness) regulate FA dynamics in VSMC. Methods: To induce actin CK remodelling rVSMC were stimulated with Noradrenaline (NA; 1.5 µM or 15 µM) or treated with blebbistatin (myosin II inhibitor, 50 µM). To alter extracellular stiffness rVSMC were cultured on substrates of varying stiffness; soft, 2.61±0.82 kPa; stiff, 40.40±2.39 kPa; glass- 50–90 GPa. Hic-5 and actin filament distribution were determined using immunofluorescence. Results: NA induced a decrease in Hic-5 in FAs (p≤0.01) and redistribution of actin filaments to the cell periphery. Blebbistatin also induced a decrease in Hic-5 in FAs and actin filament redistribution to the cell periphery (p≤0.0001). Hic-5 in FAs increased (p≤0.0001) and actin CK remodelling occurred with increasing substrate stiffness. Conclusion: Actin CK and FA structure is dynamically regulated in response to alterations in intra- and extracellular forces in VSMC. Hic-5 redistribution in response to vasoconstrictor and mechanical stimuli implicates Hic-5 in FA remodelling and mechanosensing in VSMC. Altered Hic-5 function may contribute to arterial remodelling in cardiovascular disease.